Cape Verde : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1996)
This paper describes economic developments in Cape Verde during 1990-96. After a noticeable slowdown during 1989-91, the Cape Verdean economy rebounded in 1992 and continued to expand in 1993-95, prompted by a sustained increase in public spending and the positive effects of a liberalization of economic activities. Real GDP growth averaged 4 percent during 1992-95, but domestic, economic, and financial developments were characterized by increasing imbalances. Total government expenditure increased rapidly, reaching on average 60.1 percent of GDP in 1994-95, far outpacing any growth in domestic revenues and external grants.